Effects of foreign direct investment and trade on labor productivity growth in Vietnam - Hidekatsu Asada (Journal of Risk and Financial Management, 2020)
Among developing Asian countries that have accelerated their integration with the global economy, Vietnam has achieved remarkable economic development. Vietnam's development strategy prioritizing the promotion of trade and foreign direct investment (FDI) resulted in the rapid transformation of its industrial structure from an agro-based one to one led by the export-oriented manufacturing sector in the past three decades. Given the importance of labor productivity growth on the structural transformation, the study examined the effects of FDI and trade on labor productivity growth in Vietnam in the long run and short run. The study employed the autoregressive distributed lag (ARDL) model of analysis using data from 1990 to 2017. The ARDL model analysis revealed that FDI, capital goods import, and export unanimously contributed to the labor productivity growth in the long run, while the impact in the short run remained ambiguous. The results confirm the theoretical framework augmenting the positive relationship that exists between FDI and trade and labor productivity growth. Vietnam's experience is expected to provide an important lesson to other developing countries.
Keywords: 330; Vietnam; foreign direct investment; labor productivity; trade